Religion and the American Civil War - Miller, Randall M.; Stout, Harry S.; Wilson, Charles Reagan (Oxford University Press, 1998)
The 16 essays in this volume address the question of the role played by religion in the American Civil War. The authors show that religion, understood in its broadest context, as a culture and community of faith, was found wherever the war was found. Comprising essays by such scholars as Elizabeth Fox-Genovese, Drew Galpin Faust, Mark Noll, Reid Mitchell, Harry Stout, and Bertram Wyatt-Brown, and featuring an afterword by James McPherson, this collection uncovers much of this neglected aspect of American history.; This book is intended for students and scholars of American religion and American history.